Adipocyte Specific HO-1 Gene Therapy Is Effective in Antioxidant Treatment of Insulin Resistance and Vascular Function in an Obese Mice Model - Shailendra P. Singh; Menachem Greenberg; Yosef Glick; Lars Bellner; Gaia Favero; Rita Rezzani; Luigi Fabrizio Rodella; Kevin Agostinucci; Joseph I. Shapiro; Nader G. Abraham (MDPI AG, 2020)
Obesity is a risk factor for vascular dysfunction and insulin resistance. The study aim was to demonstrate that adipocyte-specific HO-1 (heme oxygenase-1) gene therapy is a therapeutic approach for preventing the development of obesity-induced metabolic disease in an obese-mice model. Specific expression of HO-1 in adipose tissue was achieved by using a lentiviral vector expressing HO-1 under the control of the adiponectin vector (Lnv-adipo-HO-1). Mice fed a high-fat diet (HFD) developed adipocyte hypertrophy, fibrosis, decreased mitochondrial respiration, increased levels of inflammatory adipokines, insulin resistance, vascular dysfunction, and impaired heart mitochondrial signaling. These detrimental effects were prevented by the selective expression of HO-1 in adipocytes. Lnv-adipo-HO-1-transfected mice on a HFD display increased cellular respiration, increased oxygen consumption, increased mitochondrial function, and decreased adipocyte size. Moreover, RNA arrays confirmed that targeting adipocytes with HO-1 overrides the genetic susceptibility of adiposopathy and correlated with restoration of the expression of anti-inflammatory, thermogenic, and mitochondrial genes. Our data demonstrate that HO-1 gene therapy improved adipose tissue function and had positive impact on distal organs, suggesting that specific targeting of HO-1 gene therapy is an attractive therapeutic approach for improving insulin sensitivity, metabolic activity, and vascular function in obesity.